THE SOCIAL NECESSITY AND PRACTICAL SITUATION OF DEVELOPING STUDENTS' COMMUNICATION CULTURE BASED ON AN INTEGRATIVE APPROACH IN A GLOBAL EDUCATIONAL ENVIRONMENT (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article presents some thoughts on the pedagogical conditions for developing students' communication culture on the basis of an integrative approach in a global educational environment. The article also presents thoughts on the role of an integrative approach in improving communication culture, and the system of disciplines for developing students' communication competence on the basis of an integrative approach.